2000
DOI: 10.1136/vr.146.10.269
|View full text |Cite
|
Sign up to set email alerts
|

Veterinary education and students' attitudes towards animal welfare

Abstract: Veterinary students at two British universities in their first preclinical, first clinical and final years of study, completed questionnaires designed to assess their attitudes towards the welfare of animals. These attitudes were divided into their two constituent components: emotional (emotional empathy with animals) and cognitive (belief in the sentience of animals). Analyses of variance revealed that the year of study was significantly related to the perceived sentience of dogs, cats and cows, with students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
158
2
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(179 citation statements)
references
References 16 publications
17
158
2
2
Order By: Relevance
“…One possible explanation for this low rating is that the way this topic is worded may not convey the strong feelings, political pressures, and community opinions that often arise concerning animal welfare. The finding that this was rated lower in senior students is consistent with the known lower levels of empathy toward animals in students in the later years of their program, 21,22 particularly in male students, 13 though there may be important geographical variations 23 and variations for different classes of animals. 24 This apparent desensitization may be a protective mechanism to avoid moral distress, a characteristic that has been identified by veterinary practitioners and students.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…One possible explanation for this low rating is that the way this topic is worded may not convey the strong feelings, political pressures, and community opinions that often arise concerning animal welfare. The finding that this was rated lower in senior students is consistent with the known lower levels of empathy toward animals in students in the later years of their program, 21,22 particularly in male students, 13 though there may be important geographical variations 23 and variations for different classes of animals. 24 This apparent desensitization may be a protective mechanism to avoid moral distress, a characteristic that has been identified by veterinary practitioners and students.…”
Section: Discussionsupporting
confidence: 82%
“…11 Engaging veterinary students in interactive activities based on moral development theory and ethical decision making can develop their moral judgment skills, 12 and may help to counter the desensitization of students during their veterinary training. 13,14 Similar research in the Box 1: Key AWE topics selected for inclusion in the questionnaire…”
Section: Introductionmentioning
confidence: 99%
“…Thus more young female veterinarians identify with ''The Supporter of the Responsible Farmer'' and ''The Professional Veterinarian''; young male veterinarians identify more with 'Animals' Advocates' and ''The Situational, Pragmatic and Intuitive Veterinarians.'' Earlier studies also found correlations among veterinary students between moral reasoning or the human-animal bond and gender (Self et al, 1996;Williams et al, 1999;Paul and Podberscek, 2000;Martin et al, 2003).…”
mentioning
confidence: 99%
“…11 Analyses of variance revealed that year of study was significantly related to students' perception of the sentience of dogs, cats, and cows: students in later years of study rating these animals as having lower levels of sentience. Female students rated themselves as having significantly higher levels of emotional empathy with animals than did the male students.…”
Section: Discourses On Veterinary Students and Their Triangular Relatmentioning
confidence: 99%
“…This is surprising, since other studies have found correlations, among veterinary students, between moral reasoning or the human-animal bond and gender. [7][8][9][10]11,12 It must be noted however, that few men participated in this study, since approximately 80% of current Dutch veterinary students are female.…”
Section: Conclusion About Gender and Workplace Preferencementioning
confidence: 99%